2006
DOI: 10.1038/sj.ejcn.1602445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-fat hard cheese enriched with plant stanol esters on serum lipids and apolipoprotein B in mildly hypercholesterolaemic subjects

Abstract: Objective: To investigate the cholesterol-lowering effects of a low-fat cheese enriched with plant stanol esters in mildly hypercholesterolaemic subjects, as part of their normal diet. Design: A randomized double-blind parallel-group study. Setting: Valio Ltd, Helsinki. Subjects: Sixty-seven mildly hypercholesterolaemic volunteers (24 men, 43 women) participated in the study, which all of them completed. Interventions: The subjects were randomly assigned to the plant stanol ester group or the control group. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The LDL-cholesterol lowering effect of plant stanol esters added to margarine-type spreads, mayonnaise and yoghurt was consistent and of similar magnitude among the studies. Similar results were also obtained for butter, low fat cheese, "ready-made low fat meals" and for pasta, each of them used as the vehicle in a single study (Gylling and Miettinen, 1999;Jauhiainen et al, 2006;Salo and Wester, 2005). Some studies suggested that the LDL-cholesterol lowering effect might be smaller when stanol esters were administered in soft gel capsules, milk and muesli, compared to margarine-type spreads (Lagstroem et al, 2006;Seppo et al, 2007;Theuwissen and Mensink, 2007;Woodgate et al, 2006).…”
Section: Ldl-cholesterol Lowering Effectsupporting
confidence: 56%
“…The LDL-cholesterol lowering effect of plant stanol esters added to margarine-type spreads, mayonnaise and yoghurt was consistent and of similar magnitude among the studies. Similar results were also obtained for butter, low fat cheese, "ready-made low fat meals" and for pasta, each of them used as the vehicle in a single study (Gylling and Miettinen, 1999;Jauhiainen et al, 2006;Salo and Wester, 2005). Some studies suggested that the LDL-cholesterol lowering effect might be smaller when stanol esters were administered in soft gel capsules, milk and muesli, compared to margarine-type spreads (Lagstroem et al, 2006;Seppo et al, 2007;Theuwissen and Mensink, 2007;Woodgate et al, 2006).…”
Section: Ldl-cholesterol Lowering Effectsupporting
confidence: 56%
“…Another characteristic of the product tested in the present study is its very low fat content. In previous studies of "low-fat" dairy products (6,10,20), the fat content of the products tested was often relatively low but higher than that in the present study. The main dietary recommendation for patients with hypercholesterolemia is to limit their intake of saturated fats, including those of dairy products.…”
Section: Tablementioning
confidence: 85%
“…Compared to control, LDL levels were reduced by 0.33 (95% CI, –0.38 to –0.28), 0.32 (95% CI, –0.40 to –0.25), –0.34 (95% CI, –0.40 to –0.28) and 0.20 (95% CI, –0.28 to –0.11) mmol/L in the fat spreads, mayonnaise and salad dressing, milk and yoghurt, and other food products, respectively. Other food product subgroups included studies testing the efficacy of plant sterols/stanols incorporated in chocolate ( 47 , 48 ), orange juice ( 22 , 23 ), cheese (49) , non-fat beverage ( 26 , 27 ), meat (33) , croissants and muffins (21) , oil in bread (43) , and cereal bars (24) .…”
Section: Resultsmentioning
confidence: 99%